2021
DOI: 10.1155/2021/6629951
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Protein Profile and Food Intake: A Dietary Pattern Analysis

Abstract: Saliva research has gained interest due to its potential as a source of biomarkers. One of the factors inducing changes in saliva, in the short term, is food intake, and evidence exist about changes in salivary proteome induced by some food components. Since this topic of research is in its early stages, it was hypothesized that saliva protein composition could be associated with different levels of adherence to dietary patterns that contain higher amounts of plant products. The aim of the present study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Dietary patterns determine changes in saliva composition [ 145 ]. For example, a liquid diet may significantly alter saliva’s protein composition by reducing protein and electrolyte concentrations [ 146 ].…”
Section: How Does Inadequate Protein Intake Affect Saliva and Oral He...mentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary patterns determine changes in saliva composition [ 145 ]. For example, a liquid diet may significantly alter saliva’s protein composition by reducing protein and electrolyte concentrations [ 146 ].…”
Section: How Does Inadequate Protein Intake Affect Saliva and Oral He...mentioning
confidence: 99%
“…For example, a liquid diet may significantly alter saliva’s protein composition by reducing protein and electrolyte concentrations [ 146 ]. Diets high in vegetables, fruit and high-protein food are associated with changes in the salivary proteome [ 145 ]. As stated in the introduction, saliva is composed of numerous defence proteins involved in both innate and acquired immunity [ 147 ].…”
Section: How Does Inadequate Protein Intake Affect Saliva and Oral He...mentioning
confidence: 99%
“…The study by Louro et al. (2021) on individual variations in the perception of basic tastes and astringency of fruits and vegetables showed that individuals who are more sensitive to perception prefer the sweet taste of fruits. Moreover, individuals with higher BMI are less sensitive to acidic taste (Simchen et al., 2006).…”
Section: Resultsmentioning
confidence: 99%
“…It is a tactile sensation felt as a rough, dry sensation in the mouth, which is usually due to the interaction of polyphenols (mainly tannins) with salivary proteins (Huang & Xu, 2021). The intake of foods rich in these compounds may be related to a greater or lesser perception of this sensory attribute (Louro et al., 2021), that is, the lower the consumption of fruits and vegetables, the lower the perception of the astringent stimulus.…”
Section: Resultsmentioning
confidence: 99%
“…More than 1000 unique human salivary proteins were identified by high-throughput proteomic technologies and are deposited in the Human Salivary Proteome Wiki . Salivary composition is dynamic and may be influenced by external and internal factors, such as diet and diseases. In this study, 278 proteins were identified in non-processed saliva. The identified proteins reduced to 222 and 219 for 0.22 and 0.45 μm filtered saliva, respectively, and to 201 for pasteurized saliva.…”
Section: Discussionmentioning
confidence: 95%